2015
DOI: 10.1039/c4ob02389g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed unactivated β-methylene C(sp3)–H bond alkenylation of aliphatic amides and its application in a sequential C(sp3)–H/C(sp2)–H bond alkenylation

Abstract: A palladium(II)-catalyzed β-methylene C(sp(3))-H bond alkenylation of acyclic aliphatic amides with alkenyl halides has been developed. Both (E)-olefins and (Z)-olefins can be readily accessed using this method and a possible (Z)/(E)-olefin isomerization pathway is proposed. A solvent effect-promoted sequential C(sp(3))-H bond alkenylation and C(sp(2))-H bond alkenylation was also studied, and can provide a convenient route to novel diene compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Access to linear E -olefins from E -iodo alkenes and Z -isomers from Z -olefins was obtained, albeit with moderate E / Z ratios in the latter case ( Scheme 81A ). 485 …”
Section: Bidentate Dgsmentioning
confidence: 99%
“…Access to linear E -olefins from E -iodo alkenes and Z -isomers from Z -olefins was obtained, albeit with moderate E / Z ratios in the latter case ( Scheme 81A ). 485 …”
Section: Bidentate Dgsmentioning
confidence: 99%
“…Daugulis and co-workers first observed that 8-aminoquinoline amides can serve as ad irecting group for this purpose, whereby a b-methylene CÀHbond of amide 101 is arylated to afford 102 (Scheme 17). [14] Thei ncorporation of various functional groups at these CÀHb onds has been rendered possible as ar esult of the contributions of different research groups.For the formation of C À Cbonds,the alkylation of 103, the alkynylation of 106,a nd the alkenylation of 109 and 101 were developed by the groups of Daugulis, [49] Tobisu and Chatani, [50] Chen, [51] and Rao, [52] respectively.The geometry of vinyl iodide 110 is preserved in Chenss ystem during the alkenylation of amide 109.…”
Section: Carbonyl Groups (8-aminoquinoline Amides)mentioning
confidence: 99%
“…However, the substrate scope was limited to aliphatic acids with a β-quaternary centre, due to the well-known Thorpe–Ingold effect in cyclopalladation17, and ratios of mono- to diarylated products in the range 2.5:1 to 5:1 were observed. Thus, the use of various directing groups to achieve regioselective β-C( sp 3 )–H bond functionalization of carboxylic acid derivatives18192021222324252627282930313233343536373839404142434445 has been extensively explored in the past decades (Fig. 1).…”
mentioning
confidence: 99%
“…In the same year, Daugulis reported the well-known bidentate directing group 8-aminoquinoline, which has been demonstrated to have excellent ability in assisting β-C( sp 3 )-H arylation of carboxylic acids20. Since then, a number of β-C( sp 3 )-H functionalization reactions, such as arylation212223, alkenylation24, alkylation2526, alkynylation2728, alkoxylation29, amination30 and so on3132333435, employing various transition metal catalysts, have been developed. Inspired by the assisting ability of 8-aminoquinoline, researchers developed a series of N , N -bidentate directing groups for site-selective C( sp 3 )–H bond functionalization in aliphatic acids, which provided various approaches in the synthesis of important synthetic units (Fig.…”
mentioning
confidence: 99%